From Canton Restaurant to Panda Express : a history of Chinese food in the United States / Haiming Liu - Liu, Haiming
"The story of Chinese Americans through the lens of food. From Canton Restaurant in 1849 to Panda Express today, Chinese food history in America spans over 150 years. Chinese 'Forty-niners' were mostly merchants and restaurateurs who migrated here not to dig gold but to do trade. Racism against the Chinese slowed down the growth of the Chinese restaurant business in the late 19th century, but it made a rebound in the format of chop suey. From 1900 to the 1960s, chop suey as imagined authentic Chinese food attracted numerous American customers including Jewish Americans as its collective fan. Then the real Chinese food such as Hunan, Sichuan or Shanghai cuisine replaced chop suey houses in the 1970s following the arrival of new Chinese immigrants after immigration reform in 1965. Those regional-flavored Chinese restaurants were brought in and established by immigrants from Taiwan rather than mainland China. As Chinese restaurants in America turned Chinese in flavor, P.F. Chang's and Panda Express rose fast in the 1990s to meet the need of constantly changing and often multi-ethnically blended eating habits of American customers. Chinese food in America is a fascinating history about both Chinese and Americans. Embedded in this history is the story of human migration, culinary tradition, racial politics, ethnic identity, cultural negotiation, Chinese Diaspora and transnational life, and Chinese cuisine as a global food. Though a scholarly work, this book aims at all readers who are interested in food history and culture"--Provided by publisher